Endowment effect in Latin America: experimental evidence - Manzur, Enrique; Olavarrieta, Sergio; Hidalgo, Pedro; Farías, Pablo (Estudios de Administración, 2017)
Authors from several disciplines - decision sciences, management, marketing, behavioral economics - have documented the existence of anomalies to the standard rational model of human behavior. Among several anomalies, the endowment effect is a key finding of this previous research. Few studies have explored the endowment effect in developing countries. This study reports the results of an experiment conducted in Chile to empirically analyze the endowment effect. Findings are consistent with previous international evidence suggesting that ownership itself produces value to consumers (and decision makers). Implications for marketing, management, business education and policy making practices are briefly presented.